The effect of a cationic salt on the photoinitiated polymerization of methyl methacrylate - Arsu, N; Aydin, M (ELSEVIER SCIENCE SA, 1999)
The photoinduced free radical polymerization of methyl methacrylate in the presence of benzophenone and thiophenoxyacetic acid were investigated. It has been observed that adding of diphenyliodoniumhexafluorophosphate (Ph2I+ PF6) salt increased tr re rate of polymerization and molecular weight of polymer. (C) 1999 Elsevier Science S.A. All rights reserved.
Keywords: Chemistry